Development of Mellorine from Darsono Guava (Syzygium Malaccense) with the Addition of Virgin Coconut Oil (VCO) and Inulin - Regita Widya Pramesti; Rosida; Anugerah Dany Priyanto (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Darsono guava (Syzygium malaccense) is a local fruit rich in fiber and bioactive compounds; however, its utilization remains limited. The development of mellorine as a low-fat imitation ice cream represents an alternative approach to diversifying local fruit-based products. This study aimed to determine the effect of adding virgin coconut oil (VCO) and inulin on the physicochemical and organoleptic properties of prebiotic darsono guava mellorine, as well as to identify the best treatment that produces optimal characteristics and is preferred by consumers. The study was conducted using variations in the addition of VCO and inulin. The observed parameters included physicochemical properties, namely protein content, fat content, total sugar, dietary fiber, viscosity, overrun, total soluble solids, and melting time, as well as organoleptic properties including color, aroma, taste, and texture. Data were analyzed using analysis of variance (ANOVA), followed by post hoc tests and decision analysis to determine the best treatment. The best treatment was obtained with the addition of 14% VCO and 4% inulin, resulting in mellorine with fat content of 7.23%, dietary fiber of 5.05%, total soluble solids of 30.25%, overrun of 50.33%, viscosity of 1621 mPa·s, and melting time of 31 minutes. The product also exhibited antioxidant activity of 60.70%, vitamin C content of 14.09 mg, protein content of 2.95%, and total sugar of 22.51%. Organoleptic evaluation showed scores of 3.56 (slightly liked) for taste, 3.48 (slightly liked) for aroma, 3.96 (liked) for color, and 3.52 (slightly liked) for texture. Overall, the selected treatment produced mellorine with good physicochemical characteristics and a relatively high level of consumer acceptance, indicating its potential to be developed as a functional food product based on local fruit. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-beingSDG 12: Responsible Consumption and Production